2015
DOI: 10.1186/s12989-016-0145-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulmonary and systemic toxicity following lung exposure to graphite nanoplates: a member of the graphene-based nanomaterial family

Abstract: Background: Graphene, a monolayer of carbon, is an engineered nanomaterial (ENM) with physical and chemical properties that may offer application advantages over other carbonaceous ENMs, such as carbon nanotubes (CNT). The goal of this study was to comparatively assess pulmonary and systemic toxicity of graphite nanoplates, a member of the graphene-based nanomaterial family, with respect to nanoplate size. Methods: Three sizes of graphite nanoplates [20 μm lateral (Gr20), 5 μm lateral (Gr5), and <2 μm lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…In contrast, researchers at the US National Institute of Occupational Safety and Health (NIOSH) typically use doses under 100 mg/mouse for pharyngeal aspiration studies of nanoparticles as these doses usually fall below lung overload in the mouse model. At a carbon black (Printex 90) dose of 40 mg/mouse, Roberts et al (2016) found increased but transient inflammation in the lung. While the use of a high dose indicates that it may be possible to evoke certain adverse effects, the interpretation of such findings for hazard identification and human risk assessment is not clear because of the generation of potential artifactual effects.…”
Section: Evaluation Of Studiesmentioning
confidence: 93%
“…In contrast, researchers at the US National Institute of Occupational Safety and Health (NIOSH) typically use doses under 100 mg/mouse for pharyngeal aspiration studies of nanoparticles as these doses usually fall below lung overload in the mouse model. At a carbon black (Printex 90) dose of 40 mg/mouse, Roberts et al (2016) found increased but transient inflammation in the lung. While the use of a high dose indicates that it may be possible to evoke certain adverse effects, the interpretation of such findings for hazard identification and human risk assessment is not clear because of the generation of potential artifactual effects.…”
Section: Evaluation Of Studiesmentioning
confidence: 93%
“…Along with this great interest in GBM, a number of recent studies have also been published on the important issue of the toxicology of GBM [68]. Since GBM are also now available from commercial sources, it is important to characterize the properties of these commercial samples of GBM.…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that a large accumulation of eosinophils in BALF was observed on OVA sensitization in OVA/ALL mice before GO administration. Similar study was performed by Roberts et al (2016), where mice were exposed by pharyngeal aspiration to 3 lateral sizes of graphite nanoplates (20 µm (Gr20), 5 µm (Gr5), and <2 µm (Gr1) at doses of 4 or 40 μg/mouse. At 4 h, 1 day, 7 days, 1 month, and 2 months after exposure, bronchoalveolar fluid was collected and cells were used for analysis of lung injury and inflammation.…”
Section: Monocytes Neutrophils Eosinophils Nk Cells and Mast Cellsmentioning
confidence: 76%